IMPLEMENTASI LOGIKA FUZZY PADA GAME RPG PERANG BARATAYUDA - Harsadi, Paulus; Saptomo, Wawan Laksito Yuli (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2023)
Indonesia is a country that has many cultures in it. Javanese Puppet is one of the Indonesian cultural arts that is growing rapidly on the islands of Java and Bali. Javanese Puppet stories have been used as material for Javanese language lessons in Indonesian schools, especially on the island of Java. However, these stories seem to be starting to be forgotten following the increasing age of the community and also the declining public interest in them. The purpose of this research is to create an RPG game using one of the Javanese puppet stories called the Baratayuda War by using the help of Sugeno's Fuzzy logic implementation in making artificial intelligence on enemy characters. The data collection method uses the Literature Study method which is carried out to obtain information and references from books, papers and scientific journals. From the results of testing the calculation of enemy character variable data consisting of Life, Distance and Ammunition variables, it is evident that Sugeno's Fuzzy logic has been successfully used in determining the behavior of enemy characters. The results of the highest percentage of enemy behavior obtained were 42 % attacking behavior by Striker-type enemies, 35 % attacking behavior by Archer-type enemies and 67% aggressive behavior by Leader-type enemies. From the questionnaires collected by researchers to users of the Baratayuda War game, the overall average result was 86.4%, so that the use of the Baratayuda War game was included in the Very Good category.